Efektivitas Antidiabetes Ekstrak Bribil (Galinsoga parviflora) pada Tikus (Rattus norvegicus) Model Diabetes Melitus Tipe 2 - Samosir, Monicha Desry; Listyawati, Shanti; Widiyani, Tetri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to examine the effectiveness of G. parviflora extract in reducing fasting blood glucose (FBS) levels and improving lipid profiles. The research design used was a laboratory experiment with a Completely Randomized Design (CRD). This study was conducted from June 2024 to January 2025 in the Laboratory of Biology Study Program and Integrated Mathematics and Natural Sciences Laboratory. Rats were divided into five groups, namely negative control, positive control (glibenclamide 5 mg/kgBB), and three treatment groups of bribil extract with doses of 400 mg/kgBB, 600 mg/kgBB, and 800 mg/kgBB. Parameters measured included GDP levels and lipid profiles (total cholesterol, triglyceride, HDL, and LDL levels). Data analysis was performed using one-way ANOVA test and Tukey's Post Hoc further test. The results showed that the ethanol extract of bribil (Galinsoga parviflora) doses of 600 and 800 mg/kgBB effectively reduced GDP levels, total cholesterol levels, triglyceride levels, LDL levels, and HDL levels of rats (Rattus norvegicus) T2DM model. These results indicate that bribil extract has potential as a therapeutic agent for T2DM. These findings suggested the possibility of Galinsoga parviflora extract as a DMT2 therapeutic agent.